2011
DOI: 10.1016/j.gca.2011.01.004
|View full text |Cite
|
Sign up to set email alerts
|

Carbon dioxide in silicate melts: A molecular dynamics simulation study

Abstract: The distribution, recycling and storage of carbon in the Earth are of fundamental importance to understand the global carbon cycle between the deep Earth and near surface reservoirs. Degassing of CO2 at mid-ocean ridges may give information on the source region but the very low solubility of CO2 in tholeitic basalts has for consequence that near all Mid-Ocean Ridge Basalts glasses exsolve their CO2 rich vapor at shallow depth as they approach the ocean floor. Hence their CO2 contents mostly represent the press… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

15
124
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 91 publications
(150 citation statements)
references
References 171 publications
(341 reference statements)
15
124
2
Order By: Relevance
“…Stolper (1985, 1986 and thereafter many others: see the excellent summary in Guillot and Sator 2011) suggest, from FTIR studies of quenched glass experimental run products, that carbon dioxide exists in the melt as two distinct species: molecular CO 2 and carbonate ions, the latter presumably associated principally with alkali metal and alkali earth cations. Theirs and subsequent studies also infer the predominance of molecular CO 2 in rhyolitic and more siliceous compositions with increasing importance of carbonate at decreasing SiO 2 concentration.…”
Section: Carbon Dioxide Solubility In Silicate Liquidsmentioning
confidence: 98%
See 2 more Smart Citations
“…Stolper (1985, 1986 and thereafter many others: see the excellent summary in Guillot and Sator 2011) suggest, from FTIR studies of quenched glass experimental run products, that carbon dioxide exists in the melt as two distinct species: molecular CO 2 and carbonate ions, the latter presumably associated principally with alkali metal and alkali earth cations. Theirs and subsequent studies also infer the predominance of molecular CO 2 in rhyolitic and more siliceous compositions with increasing importance of carbonate at decreasing SiO 2 concentration.…”
Section: Carbon Dioxide Solubility In Silicate Liquidsmentioning
confidence: 98%
“…Indeed, that assumption has proved successful in previous models of CO 2 solubility in silicate liquids (Spera and Bergman 1980;Papale 1997Papale , 1999Papale et al 2006;Duan 2014), although alternate formulations that embody speciation (e.g., Dixon et al 1995;Newman and Lowenstern 2002) are equally effective. The recent molecular dynamics study of Guillot and Sator (2011) has explored molecular and carbonate speciation as a function of T, P, and composition. They find that increasing temperature stabilizes the carbonate species as does pressure, but that in simulations for kimberlitic, basaltic, and rhyolitic composition liquids below 2 GPa (all at a temperature of 2000 K), molecular CO 2 is the predominant melt species-essentially controlling the solubility of dissolved carbon dioxide.…”
Section: Carbon Dioxide Solubility In Silicate Liquidsmentioning
confidence: 99%
See 1 more Smart Citation
“…More recently, however, it has been shown that at high temperature depolymerized melts contain substantial molecular CO 2 (Nowak et al 2003;Ni and Keppler 2013) and that at high pressure polymerized melts contain significant amounts of the carbonate ion (e.g., Mallik and Dasgupta 2014). Although numerous experimental studies show that the solubility of the CO 2 component is highest in depolymerized melts and increases with the abundance of non-bridging oxygens (NBO) relative to T (tetrahedral) sites in the melt (e.g., Mysen et al 1975;Brey and Green 1975;Eggler 1978;Spera and Bergman 1980;Pan et al 1991;Thibault and Holloway 1994;Behrens et al 2004Behrens et al , 2009Vetere et al 2014), a more recent molecular dynamic simulation (Guillot and Sator 2011) shows that at high pressure (~10 GPa) and high temperature (~2000 °C), there is only a weak dependence of silicate melt composition on bulk CO 2 solubility.…”
Section: Application To Natrocarbonatite Liquidsmentioning
confidence: 99%
“…b Same as a except converted to density by dividing V CO 2 and V H 2 O into their respective molecular weights (44.01 and 18.015 g/mol) 3 Page 14 of 18 ions, although there are conflicting results on the order of importance. There is widespread agreement that Mg 2+ , Ca 2+ , Na + , and K + have the strongest effect on increasing the solubility of carbonate in silicate melts, although their relative effect is debated (e.g., Dasgupta et al 2007;Moore 2008;Behrens et al 2009;Lesne et al 2011;Guillot and Sator 2011;Iacono-Marziano et al 2012;Vetere et al 2011Vetere et al , 2014Morizet et al 2010Morizet et al , 2014Dasgupta 2013, 2014). It is inferred from solubility studies (e.g., Brooker et al 2001a) and phase-equilibrium results (e.g., Dasgupta 2013, 2014) that Fe 2+ is less important than the other cations, and the reason may be found in spectroscopic evidence that Fe 2+ undergoes coordination change (from sixfold to fivefold and fourfold) and enters tetrahedral (T) sites in highly depolymerized (high NBO/T) silicate melts (e.g., Brooker et al 2001b).…”
Section: Application To Natrocarbonatite Liquidsmentioning
confidence: 99%